The Online Learning Environment: A Personal Experience of Collaboration - Crosta, Lucilla (Proceedings of the International Conference on Networked Learning, 2002)
This paper underlines how CMC (Computer Mediated Communication) collaboration could enhance adult learners self-development and self growth. Assuming "Constructivism Theory" and the "Self-Directed Learner" as the basis of this personal reflection, I will highlight the two sides of the argument; my experience of collaboration was both an active, an interactive, as well as an equal process but it also required great effort and personal change. It overcame the traditional individualistic model of learning, supporting and establishing further relationships among participants. However, in my personal view, it required a more effective organizational tool, in order to overcome the sense of confusion and lack of human presence, which was strong when working collaboratively online.